Biogas Production from Water Spinach and Banana Peel Waste Using Plug Flow Reactor - Soeprijanto; Alif Adi Kaisar; Dyah Firdha Amalia (IPTEK The Journal of Engineering, 2021)
Biofuel is one of the promising energy in the future that can play an essential role in maintaining energy security in Indonesia Biogas, which is only one of many types of biofuels is considered a renewable energy source that does not contribute to the impact of greenhouse gases. The main composition of the gas consists mainly of methane (CH4), and carbon dioxide (CO2) and resembles commonly used fossil fuels such as natural gas. This study aimed to determine the method of making biogas using water spinach and banana peel waste. The process of making biogas begins with preparing the materials to be fed to the bioreactor daily. The prepared material is put into the bioreactor continuously every 24 hours. The results obtained are the C/N content of water spinach 10 while the banana peel is 42. The C/N ratio affects biogas production. The maximum production of biogas accumulation is in water spinach as raw material. On water spinach, the yield was 287.825 l/kg substrate and the average volume per day was 17.989 l/kg substrate. The banana peel yields 46,184 l/kg of the substrate and the average volume per day is 2,887 l/kg of the substrate. Based on the flame test conducted at the beginning of the week the gas produced can be burned, this occurs in all raw materials.